2012
DOI: 10.1016/j.ijgo.2012.03.038
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Impact of preoperative rectal misoprostol on blood loss during and after elective cesarean delivery

Abstract: Preoperative treatment with 400 μg rectal misoprostol significantly reduced blood loss related to elective cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…5,6 Misoprostol has been evaluated as an alternative to oxytocin during cesarean delivery, and has also been used in combination with oxytocin. [7][8][9][10][11][12][13][14][15][16][17] Two meta-analyses concluded that misoprostol was as effective as oxytocin and that the combination of the misoprostol and oxytocin is better than is oxytocin alone for the prevention of PPH. However, women with known risk factors for PPH, who are expected to benefit from an additional oxytocic agent, were excluded from some of the studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Misoprostol has been evaluated as an alternative to oxytocin during cesarean delivery, and has also been used in combination with oxytocin. [7][8][9][10][11][12][13][14][15][16][17] Two meta-analyses concluded that misoprostol was as effective as oxytocin and that the combination of the misoprostol and oxytocin is better than is oxytocin alone for the prevention of PPH. However, women with known risk factors for PPH, who are expected to benefit from an additional oxytocic agent, were excluded from some of the studies.…”
mentioning
confidence: 99%
“…However, women with known risk factors for PPH, who are expected to benefit from an additional oxytocic agent, were excluded from some of the studies. [12][13][14]16,17 Thus, the existing evidence on the optimal uterotonic agent during cesarean for high-risk women is insufficient.…”
mentioning
confidence: 99%
“…The list of studies excluded is available from the authors upon request. Seventeen studies, 38-54 including 3174 women, fulfilled inclusion criteria of which seven evaluated misoprostol versus oxytocin (n=700), 39,40,42,45,47,49,54 one evaluated misoprostol versus ergometrine (n=374), 51 eight evaluated misoprostol plus oxytocin versus oxytocin (n=1918), 41,43,44,46,48,50,52,53 and one 3-arm trial evaluated misoprostol versus oxytocin versus misoprostol plus oxytocin (n=182). 38 …”
Section: Resultsmentioning
confidence: 99%
“…The most common dose used in studies evaluating the sublingual route was 400 g, and 800 g in studies that evaluated the rectal and intrauterine routes. Misoprostol was used after delivery of the neonate in 12 studies and before delivery of the neonate in five studies (orally 38 or rectally 47 at the time of peritoneal incision, rectally just before onset of cesarean section 51 or after urinary catheter placement, 52 and sublingually after tracheal intubation 53 ). It should be noted that in seven studies that compared misoprostol with placebo, all women received an intravenous infusion of oxytocin in doses ranging from 5 IU to 20 IU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation